2011
DOI: 10.1007/s00296-011-1901-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for chronic synovitis of knee: arthroscopic or open synovectomy

Abstract: Chronic synovitis of knee joints that cannot be treated by conservative measure effectively can be treated successfully by the operations through resecting the inflamed synovium. The operations include open synovectomy and arthroscopic synovectomy. The purpose of this study is to compare the two operations in alleviating symptoms and cosmetic effect. There were 42 patients in this study, and they suffered from chronic synovitis of knee joints, including rheumatoid arthritis and non-specific synovitis. Twenty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
1
8
0
2
Order By: Relevance
“…Einem Fünftel der Betroffenen droht sogar eine langfristige Chronifizierung [15]. Sollte sich das Erkrankungsbild trotz der o. g. Behandlung therapierefraktär zeigen, stellt die arthroskopische Synovialektomie eine invasive, aber erfolgversprechende therapeutische Option dar [4,28].…”
Section: Therapie Der Reaktiven Arthritisunclassified
“…Einem Fünftel der Betroffenen droht sogar eine langfristige Chronifizierung [15]. Sollte sich das Erkrankungsbild trotz der o. g. Behandlung therapierefraktär zeigen, stellt die arthroskopische Synovialektomie eine invasive, aber erfolgversprechende therapeutische Option dar [4,28].…”
Section: Therapie Der Reaktiven Arthritisunclassified
“…Liegen keine extraartikulären Begleitpathologien vor, können Synovialektomien an fast allen Gelenken auch sehr effektiv arthroskopisch durchgeführt werden [6,[9][10][11][12]. Die Ergebnisse und Rezidivrate nach diesem Vorgehen können mit einer 6 Wochen postoperativ erfolgenden Radiosynoviorthese noch deutlich verbessert werden [13][14] Ebenfalls zu den gelenkerhaltenden Operationen gehören die knöchernen Umstellungsoperationen, z.…”
Section: Präventive Gelenkerhaltende Operationenunclassified
“…Arthroscopic synovectomy can be performed through either five or six portal approach. Previous studies have demonstrated that five portal arthroscopic synovectomy, with only five small incisions made around the knee joint, could be as effective as open synovectomy for knee synovitis from various causes ( Pan et al, 2012 ; Kubat et al, 2010 ; Jain et al, 2013 ). The benefits of five portal arthroscopic synovectomy in the treatment of knee rheumatoid arthritis require further investigations.…”
Section: Introductionmentioning
confidence: 99%